Integrated Social Welfare Data Management Policy in Tomohon City - Lasut, Thomly Stevie Ronald; Kairupan, Sisca B.; Mokat, Jetty; Mandagi, Marthinus (Technium Social Sciences Journal, 2025)
This research aims to analyze the Integrated Social Welfare Data Policy Management (DTKS). This research approach uses a descriptive qualitative approach with data collection techniques, namely observation, interviews and documentation with data analysis techniques through data reduction, data presentation and verification conclusion drawing. In the research findings involving 7 informants, that in the focus of research on the implementation of the Integrated Social Welfare Data Management program specifically in the process of inputting data on beneficiaries in the Social Empowerment and Poverty Handling Division at the Tomohon City Social Service found that there are still obstacles in the implementation of this program or policy with reference to five main sub-aspects: program socialization to technical implementers, inter-agency communication, implementer resources, funding sources, and the impact of budget revisions on program implementation. This research used a qualitative approach with a descriptive method, involving in-depth interviews with relevant parties as well as analysis of official documents as the main data source. The results showed that the lack of understanding of technical terms, network instability, and the lack of routine socialization were the main obstacles in the implementation of the program. In addition, ineffective inter-service communication, such as information delays and lack of use of digital platforms, hampers coordination in data management. Lack of competent human resources, limited technical training, and weak performance evaluation mechanisms reduce the effectiveness of program implementation. Funding constraints, such as delays in disbursement and unforeseen budget revisions, further exacerbated the smooth running of the program. The short-term solutions implemented proved inadequate to overcome these problems. This study recommends increasing the frequency of socialization and technical training, optimizing the use of digital technology in communication between agencies, and rearranging human resource management mechanisms. In addition, improving budget management through more integrated and responsive financial planning is a priority to support the sustainability of effective DTKS program implementation. The findings of this research are expected to contribute to the improvement of policy implementation and social services in Tomohon City.